The manufacturing sector in rural and township areas in Umvoti Local Municipality and Umzinyathi District, South Africa - Madonsela, Mduduzi (University of the Free State, 2024)
The low investments in the manufacturing sector in the rural and township areas at uMvoti Municipality, uMzinyathi District Municipality represent a thorny issue to the people of uMvoti Municipality and the uMzinyathi District in KwaZulu-Natal, having a dire impact on their socioeconomic well-being. Within the context of uMzinyathi District, KwaZulu-Natal in South Africa, uMzinyathi District, the study looked into more detailed information on how to address the issue of the rural and Township areas and the potential investments therein. The study revealed that rural and township economies are as important as that of the towns and cities and a shortage of investments by the government and the private sector contributes to a high level of unemployment and low activism by the economic participants, which may result in a loss of income and encouraging instability in the country.
Dissertation(MDS (Development Studies))--University of the Free State, 2024
Keywords: Manufacturing sector; Rural and township areas; Impact of low investments in these areas